Type IIIb Endoleak after Thoracic Endovascular Aortic Repair Caused by Endoanchor Dislocation - Müller-Eschner, Matthias; Peters, Andreas; Meisenbacher, Katrin; Böckler, Dittmar; Bischoff, Moritz (Annals of vascular surgery, 2015)
Background - The aim of this study was to report the occurrence of a type IIIb endoleak after endovascular repair of a thoracic aortic aneurysm caused by endoanchor dislocation. - Case Report - An 84-year-old female patient underwent thoracic endovascular repair for aneurysmal disease of her thoracic aorta. The procedure included primary left subclavian artery revascularization and the placement of endoanchors to enhance fixation of the endograft within the aortic arch. Dislocation of one of the endoanchors resulted in a graft defect leading to a type IIIb endoleak and aortic diameter expansion. - Conclusions - Endoanchors represent a promising adjunct in endovascular repair settings. However, their use requires careful procedure planning and special attention during follow-up.
Gesehen am 03.08.2020